The effect of nicotine on HPA axis activity in females is modulated by the FKBP5 genotype - Koopmann, Anne; Bez, Jennifer; Leménager, Tagrid; Hermann, Derik; Dinter, Christina; Reinhard, Iris; Schuster, Rilana; Wiedemann, Klaus; Winterer, Georg; Kiefer, Falk (Annals of human genetics, 2016)
Tobacco smoking modulates activity in the hypothalamic-pituitary-adrenal (HPA) axis and is used to cope with stress, especially by females. The single nucleotide polymorphism (SNP) rs1360780, linked to FK506-binding protein 51 (FKBP5), has been shown to affect HPA axis functioning, and has thus been suggested as a promising candidate for indicating vulnerability to stress-related disorders. The aim of this study was to investigate the interaction between nicotine consumption and rs1360780 on cortisol plasma levels in females. A total of 296 female smokers (assessed by the Fagerström Test for Nicotine Dependence; FTND) were genotyped for the SNP rs1360780. We measured participants’ cortisol plasma concentration in blood plasma collected 3 h after standardized tobacco smoking exposure. In the 36 TT-homozygotes, we found a significant negative correlation between the FTND sum score and cortisol plasma concentrations. Using linear regression analysis, we found that the FTND sum score accounted for 12.4% of the variance of cortisol plasma levels. This association was not detected in C-allele carriers. Our results suggest that nicotine is an important confounder in the modulation of HPA axis activity by FKBP5. In light of these findings, future studies on FKBP5 should seek to include data on nicotine consumption as a covariate.
Gesehen am 08.05.2019